Cardiovascular Changes in Animal Models of Metabolic Syndrome. (14th March 2013) - Lehnen, Alexandre M.; Rodrigues, Bruno; Irigoyen, Maria Cláudia; De Angelis, Kátia; Schaan, Beatriz D'Agord
Abstract : Metabolic syndrome has been defined as a group of risk factors that directly contribute to the development of cardiovascular disease and/or type 2 diabetes. Insulin resistance seems to have a fundamental role in the genesis of this syndrome. Over the past years to the present day, basic and translational research has used small animal models to explore the pathophysiology of metabolic syndrome and to develop novel therapies that might slow the progression of this prevalent condition. In this paper we discuss the animal models used for the study of metabolic syndrome, with particular focus on cardiovascular changes, since they are the main cause of death associated with the condition in humans.